MEMBANGUN KESADARAN HUKUM MELALUI PENDIDKAN ISLAM MULTIKULTURAL: ANALISIS FENOMENA DAN DAMPAK PERNIKAHAN SIRRI DI DESA GRUJUGAN - wahyudi; Khoir, Qoidul (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research aims to analyze the phenomenon of sirri marriage in Grujugan Village and explore the role of multicultural Islamic education in building community legal awareness. Using qualitative methods with a case study approach, data were collected through in-depth interviews, participatory observation, and documentation studies. Thematic analysis was applied to identify the factors causing sirri marriages, their impact on individuals and communities, as well as the contribution of multicultural Islamic education in enhancing legal understanding. The research results show that economic, social, cultural factors, and a lack of legal understanding are the main drivers of the sirri marriage practice. The impacts include unclear legal status, potential family conflicts, and social stigma. Multicultural Islamic education plays a significant role in instilling values of tolerance and justice, enhancing understanding of marriage laws, and strengthening individual character and morality. Thus, multicultural Islamic education is expected to be an effective solution in reducing the practice of sirri marriages and increasing legal awareness among the community in Grujugan Village.